Primary Diffuse Large B-Cell Lymphoma Localized to the Lacrimal Sac: A Case Presentation and Review of the Literature - Kevin Zarrabi; Ved Desai; Brandom Yim; Theodore G. Gabig (Case Reports in Hematology)
We report a rare case of diffuse large B-cell lymphoma (DLBCL) of the lacrimal sac in a 50-year-old male. The incidence of primary ocular lymphoma is low and it is considered a rare disease. Moreover, reports of ocular DLBCL are uncommon and the disease remains poorly characterized. Our patient presented for management of osteomyelitis and was incidentally found to have a painless swelling and cyst around his right eye. A PET/CT scan revealed hypermetabolic activity within the lacrimal sac and a subsequent excisional biopsy of the mass yielded histopathology consistent with DLBCL. Consequently, the patient underwent treatment with R-CHOP therapy. The patient responded well to chemotherapy with a substantial shrinkage in tumor burden and the disease remained localized. Herein, we present a rare case of primary ocular lymphoma, highlight the importance of early diagnosis, and review current treatment modalities.